A method to estimate strain in the breast during exercise - Haake, S.; Scurr, J. (Sports Engineering, 2011)
The purpose of this study was to determine a way of estimating the strain of the breast during exercise and to enable an engineering analysis of breast motion. Three participants exercised on a treadmill wearing a sports bra, an everyday bra or no bra and the motion of the body and the nipple were recorded using a 200 Hz passive marker motion capture system. Each participant also performed a breast drop test to determine the neutral position of the nipple; this allowed strains to be estimated from the point when nipple acceleration was approximately that due to gravity. Wearing any bra reduced the strain at the nipple by lifting the breast mass up towards the neutral position where the skin of the breast was neither in tension nor in compression. Non-linearities in strain occurred during the downward phase of running at strain values exceeding the static value at up to 70% strain; these were consistent with the previous studies on skin. It was postulated that comfort scores might be related to elements of the acceleration-strain curve and that nipple motion causing strain beyond static strain might be an important parameter in understanding breast pain.